IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT BY PEER FEEDBACKING AT FACEBOOK GROUP - Gilar Ferisa (Journal of English Education Program (JEEP), 2019)
The present study deals with improving students’ achievement in writing narrative text by peer feedbacking at facebook group. Peer feedback is feedback that is given by peer. This study was attempted to find out the difference of students’ achievement in writing narrative text between students who are taught by peer feedbacking at facebook group and those who are not. This study also was attempted to find out the students’ responses toward peer feedbacking at facebook group. This study was conducted at the eleventh grade students of SMAN 1 Kawali. The result of computation showed that t-observed was 2.234 and t-table was 2.021 at the level of significance 0.05 and df=38. It means t-observed was higher than t-table. It was enough to accept the alternative hypothesis (H1), that there is a significant difference of students’ achievement in writing narrative text between students who are taught by peer feedbacking at facebook group and those who are not. In qualitative study, the writer administered a questionnaire to the experimental group to discover their responses toward peer feedbacking at facebook group. The result of questionnaire analysis showed that the students gave positive responses toward peer feedbacking at facebook group in learning writing narrative text. The positive responses itself supported the quantitavie result, that peer feedbacking at facebook group improved students’ achievement in writing narrative text.